Blockchain em governo: avaliação sociotécnica de artefatos de sistema de informação - Rodrigues, Dênis Alves (2021)
Governments have adopted Information System (IS) artifacts seeking to improve services, increase their efficiency, effectiveness, in short, focusing on overcoming the social and technical challenges that are presented to them. More recently, a disruptive technology is also being appropriated to overcome problems in the public sector, that is the Blockchain. Therefore, it is important to understand and evaluate the results of these new IS artifacts that are generated in government contexts. Contributing to fill this gap, this research develops a socio-technical model to evaluate Blockchain artifacts for Digital Government. To this end, the paradigm of Design Science Research is used and, based on the proposal of sub-artifacts by De Leoz and Petter (2018), a model for the assessment of IS artifacts in government is developed that considers the components: information, technology and social, within the context of e-government, evaluating national cases.